MOTIVASI KERJA KARYAWAN DAIMA HOTEL PADANG - Putri, Melati Rabecca; Yuliana, Yuliana; Kasmita, Kasmita (Journal of Home Economics and Tourism, 2014)
The purpose of research is to to know the employee motivation Daima Hotel Padang. This study is a descriptive correlational study. The population in this research is all employees Daima Hotel Padang. Sample selection techniques in the study using purposive sampling technique for 50 persons. Data collection techniques with a structured questionnaire based on Likert scale that has been tested for validity and reliability. Research results employee motivation Daima Hotel Padang is sufficient with an average value 108,58 in the range 105,6 – 117,4.  While based on each indicator is: 1) perseverance is sufficient with an average value 20,28 in the range 18,1 – 20,9; 2) The excitement of working is sufficient with an average value 20,28 in the range 18,1 – 20,9; 3) Spirit of work is sufficient with an average value 25,16 in the range 23,8 – 27,3; 4) Discipline of work is poorly with an average value 22,38 in the range 20,0 – 22,7; and 5) Responsibility is sufficient with an average value 20,48 in the range 19,8 – 22,2. Keywords: motivation, work, employee, hotel